2016
DOI: 10.1002/anie.201600244
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Dependent cis/trans Isomerization of Tetraphenylethene Derivatives: Consequences for Aggregation‐Induced Emission

Abstract: The isomerization and optical properties of the cis and trans isomers of tetraphenylethene (TPE) derivatives with aggregation-induced emission (AIEgens) have been sparsely explored. We have now observed the tautomerization-induced isomerization of a hydroxy-substituted derivative, TPETH-OH, under acidic but not under basic conditions. Replacing the proton of the hydroxy group in TPETH-OH with an alkyl group leads to the formation of TPETH-MAL, for which the pure cis and trans isomers were obtained and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…To expand application scope of planar rigid cores, tetrasubstituted ZnTDPP (zinc 5,10,15,20-tetrakistetra(4-cyanophenyl)porphyrin) and tetraphenylethylene (TPE) scaffolds were employed in order to explore porous materials with new functions [ 80 , 81 ]. It is well known that porphyrin and TPE derivatives have been extensively investigated in optoelectronic materials such as dye sensitized solar cells (DSSCs) [ 82 ] with high efficiency and aggregate induced emission (AIE) materials [ 83 ]. However, they were barely reported for the construction of HOF materials.…”
Section: The Main Content Of This Reviewmentioning
confidence: 99%
“…To expand application scope of planar rigid cores, tetrasubstituted ZnTDPP (zinc 5,10,15,20-tetrakistetra(4-cyanophenyl)porphyrin) and tetraphenylethylene (TPE) scaffolds were employed in order to explore porous materials with new functions [ 80 , 81 ]. It is well known that porphyrin and TPE derivatives have been extensively investigated in optoelectronic materials such as dye sensitized solar cells (DSSCs) [ 82 ] with high efficiency and aggregate induced emission (AIE) materials [ 83 ]. However, they were barely reported for the construction of HOF materials.…”
Section: The Main Content Of This Reviewmentioning
confidence: 99%
“…During the design of the probe intended to target caspase‐8, an AIEgen based on the tetraphenylethylene–thiophene (TPETH) system was employed because it possessed a large Stokes shift of 200 nm and so could avoid interference from the innate fluorescence of the screened natural products . The DIETDC peptide sequence was used.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Zhang et al elaborately designed severalT PE-based Z/E isomers, as shown in Scheme 4. [57] First, they synthesized TPETH-OH isomers, which wereo btained as am ixture and could not be separated by using column chromatography. However,t he isomersc ould be isolated by using reverse-phase HPLC with MeCN/water and 0.1% trifluoroacetic acid (TFA) as an eluent.…”
Section: Development Of Z/e Isomers Of Tpe Derivativesmentioning
confidence: 99%
“…In 2016, Zhang et al. elaborately designed several TPE‐based Z / E isomers, as shown in Scheme . First, they synthesized TPETH‐OH isomers, which were obtained as a mixture and could not be separated by using column chromatography.…”
Section: Development Of Z/e Isomers Of Tpe Derivativesmentioning
confidence: 99%